Osteochondral Allograft Transplant for Focal Cartilage Defects of the Femoral Condyles: Clinically Significant Outcomes, Failures, and Survival at a Minimum 5-Year Follow-up. Issue 2 (February 2021) - Gilat, Ron; Haunschild, Eric D.; Huddleston, Hailey P.; Tauro, Tracy M.; Patel, Sumit; Wolfson, Theodore S.; Parvaresh, Kevin C.; Yanke, Adam B.; Cole, Brian J.
Background: Osteochondral allograft (OCA) transplant for symptomatic focal cartilage defects in the knee has demonstrated favorable short- to midterm outcomes. However, the reoperation rate is high, and literature on mid- to long-term outcomes is limited. Purpose: To analyze clinically significant outcomes (CSOs), failures, and graft survival rates after OCA transplant of the femoral condyles at a minimum 5-year follow-up. Study Design: Case series; Level of evidence, 4. Methods: Review of a prospectively maintained database of 205 consecutive patients who had primary OCA transplant was performed to identify patients with a minimum of 5 years of follow-up. Outcomes including patient-reported outcomes (PROs), CSOs, complications, reoperation rate, and failures were evaluated. Failure was defined as revision cartilage procedure, conversion to knee arthroplasty, or macroscopic graft failure confirmed using second-look arthroscopy. Patient preoperative and surgical factors were assessed for their association with outcomes. Results: A total of 160 patients (78.0% follow-up) underwent OCA transplant with a mean follow-up of 7.7 ± 2.7 years (range, 5.0-16.3 years). Mean age at the time of surgery was 31.9 ± 10.7 years, with a mean symptom duration of 5.8 ± 6.3 years. All mean PRO scores significantly improved, with 75.0% of patients achieving minimal clinically important difference (MCID), and 58.9% of patients achieving significant clinical benefit for the International Knee Documentation Committee score at final follow-up. The reoperation rate was 39.4% and was associated with a lower probability of achieving MCID. However, most patients undergoing reoperation did not proceed to failure at final follow-up (63.4% of total reoperations). A total of 34 (21.3%) patients had failures overall, and the 5- and 10-year survival rates were 86.2% and 81.8%, respectively. Failure was independently associated with greater body mass index, longer symptom duration, number of previous procedures, and previous failed cartilage debridement. Athletes were protected against failure. Survival rates over time were not affected by OCA site ( P = .154), previous cartilage or meniscal procedure ( P = .287 and P = .284, respectively), or concomitant procedures at the time of OCA transplant ( P = .140). Conclusion: OCA transplant was associated with significant clinical improvement and durability at mid- to long-term follow-up, with 5- and 10-year survival rates of 86.2% and 81.8%, respectively. Maintenance of CSOs can be expected in the majority of patients at a mean of 7.7 years after OCA transplant. Although the reoperation rate was high (39.4%) and could have adversely affected chances of maintaining MCID, most patients did not have failure at long-term follow-up.